A retrospective cross-sectional study of risk factors and clinical spectrum of children admitted to hospital with pandemic H1N1 influenza as compared to influenza A. Issue 2 (11th March 2012) - Morris, Shaun K; Parkin, Patricia; Science, Michelle; Subbarao, Padmaja; Yau, Yvonne; O'Riordan, Sean; Barton, Michelle; Allen, Upton D; Tran, Dat
Abstract : Objective: To compare risk factors for severe disease as measured by admission to hospital and intensive care unit (ICU) and other clinical outcomes in children with pandemic H1N1 (pH1N1) versus those with seasonal influenza. Design: Retrospective analysis of children admitted to hospital with pH1N1 versus seasonal influenza A. Setting: Canadian tertiary referral children's hospital. Participants: All laboratory-identified cases of pH1N1 in children younger than 18 years admitted to hospital in 2009 (n=176) and all seasonal influenza A cases admitted to hospital from influenza seasons 2004–2005 to 2008–2009 (n=200). Children with onset of symptoms more than 3 days after admission were excluded. Primary and secondary outcome measures: Primary outcomes include admission to hospital and ICU and need for mechanical ventilation. Secondary outcomes include length of stay in hospital and duration of supplemental oxygen requirement. Results: Children admitted with pH1N1 were older than seasonal influenza A admissions (hospital admission: 6.5 vs 3.3 years, p<0.01; ICU admission: 7.3 vs 3.6 years, p=0.02). Children hospitalised with pH1N1 were more likely to have a pre-existing diagnosis of asthma (15% vs 5%, p<0.01); however, there was no difference in the severity of pre-existing asthma between the two groups. After controlling for obesity, asthma (OR 4.59, 95% CI 1.42 to 14.81) and age ≥5 years (OR 2.87, 95% CI 1.60 to 5.16) were more common risk factors in admitted children with pH1N1. Asthma was a significant predictor of the need for intensive care in patients with pH1N1 (OR 4.56, 95% CI 1.16 to 17.89) but not in patients with seasonal influenza A. Conclusion: While most pH1N1 cases presented with classic influenza-like symptoms, risk factors for severe pH1N1 disease differed from seasonal influenza A. Older age and asthma were associated with increased admission to hospital and ICU for children with pH1N1.